Measurement of weak non-linear response of Kevlar® fibre damaged by UV exposure - Ceravolo, Rosario; De Marchi, Andrea; Pinotti, Elena; Surace, Cecilia; Zanotti Fragonara, Luca (Elsevier, 2017)
This paper deals with a high-sensitivity method for the assessment of damage in high-strength fibres exposed to UV radiation. A recently developed experimental testing machine, based on an optical measurement system and electro-magnetic driving force, was used to characterize fibre materials. Stiffness, damping, and non-linearity were measured on several Kevlar® fibre samples previously exposed to UV light for different lengths of time. The results show that UV radiation increases the material non-linearity by amounts which can be clearly observed even at low vibration amplitudes. On the contrary, uncertainties affecting the determination of stiffness and damping with the adopted approach don’t seem to allow a similarly unambiguous UV damage assessment. Result confirm our initial hypothesis that non-linearity may be a valuable index of damage, at least in case of UV exposure, for applications in the Structural Health Monitoring (SHM) field.
Keywords: Non-linear response; Vibration based monitoring; Damping; Dynamic response; UV degradation; High-strength fibres